Film Review: An Analysis of Food Narrative in the Indian Film Lunchbox - Zhuang, Peina (Archīum Ateneo, 2024)
In the review of the Indian film The Lunchbox, Peina Zhuang shows that although food is central in human relations and social development in modern India, the transformation of food production and distribution systems at the micro level reveals, resists, and reinforces the conflicts between tradition and modernity. The food in the traditional Bombay lunch remain because of the lunchbox delivery system, but this comes at a cost. While in the very moment that it threatens traditions by, for instance, effacing the caste sources of the food, the lunchbox delivery system reifies the patriarchal relegation of women to the kitchen. Complicated in its implications, The Lunchbox is an entertaining take on India’s rapidly transforming food scene.